Occurrence and risk factors of zoonoses in dogs and owners in sertão, paraíba state, northeastern Brazil - Da Fonseca Fernandes, Annielle Regina; Da Costa, Diego Figueiredo; Pimenta, Carla Lauise Rodrigues Menezes; De Araújo, Kamila Nunes; Silva, Raizza Barros Sousa; De Melo, Marcia Almeida; Langoni, Hélio [UNESP]; Mota, Rinaldo Aparecido; De Azevedo, Sérgio Santos (Universidade Estadual de Londrina, 2018)
Seropositivity and risk factors for visceral leishmaniasis, Chagas disease, toxoplasmosis, and leptospirosis were investigated in 200 dogs and twenty-three owners in a municipality with a history of human cases of visceral leishmaniasis and toxoplasmosis in the region of Sertão, Paraíba State, Northeastern Brazil. In dogs, frequencies of 6% (95% confidence interval [CI] = 2.7-9.3%), 7.5% (95% CI = 3.8-11.2%), 18% (95% CI = 12.7-23.3%), and 14% (95% CI = 9.2-18.8%) were found for visceral leishmaniasis, Chagas disease, toxoplasmosis, and leptospirosis, respectively. An age of over 72 months and environment conditions (soil) were identified as risk factors for Leishmania chagasi infection. Free housing was identified as risk factor for Trypanosoma cruzi infection. For toxoplasmosis, free housing and contact with cats were found to be risk factors, while commercial food was a risk factor for leptospirosis. Of the twenty-three owners who agreed to participate in the study, eight were tested for leishmaniasis, three for Chagas disease, nine for toxoplasmosis, eleven for leptospirosis, and five were tested for more than one disease. Only anti-Toxoplasma gondii antibodies were found in the human population at a frequency of 44.4% (4/9); for all other diseases, all individuals were negative. The results indicate that such zoonoses are present in dogs from the studied region, but only toxoplasmosis was found in the owners. Our risk analysis suggests that cleaner soil, better storage of dog food, and avoiding free housing can reduce the risk of infection by these diseases.
Keywords: Canine; Epidemiology; Guardians; Transmissible diseases